Characteristics of the flora of fallow lands on rendzina soils on the Twardowice Plateau (Silesian Upland) - Beata Babczyńska-Sendek; Agnieszka Błońska; Joanna Hejdysz (Acta Agrobotanica, 2012)
The paper presents the results of investigations on the flora of fallow lands on rendzina soils. The research was carried out in the area of the Twardowice Plateau (the Silesian Upland) within 9 areas adjacent to xerothermic grasslands. The investigated flora consisted of 220 vascular plant species with the dominance of native taxa. Plants of xerothermic grasslands and thermophilous edges were the most numerous (32%). The dominance of Libanotis pyrenaica in 4 of the examined areas should be emphasized. The percentage of meadow species was also considerable (25%). Anthropophytes comprised 18% of the flora of fallow lands and archaeophytes prevailed among them (9%). Solidago canadensis, an invasive species, was the constant component of the investigated fallows and sometimes its coverage was remarkable. As a result of the high proportion of xerothermic and thermophilous plants, plants associated with dry soils and soils having an intermediate character between dry and fresh, as well as plants preferring slightly acidic to alkaline soils poor in nitrogen compounds predominated in the investigated fallows. Perennial plants prevailed (65%) in the studied flora and slightly more than half of the species reproduced only by seeds. Competitive plant species (C strategists) had the highest proportion (39%) and species with intermediate strategies CSR, CR and CS were also numerous. The investigations have shown that there are favourable conditions for settling and growth of many xerothermic species in the investigated fallow lands. Moreover, the neighbouring grasslands are the seed source for these areas.